Implementation of the Recommendations for RBC Transfusions for Critically Ill Children From the Pediatric Critical Care Transfusion and Anemia Expertise Initiative. (September 2018) - Steffen, Katherine M.; Bateman, Scot T.; Valentine, Stacey L.; Small, Sara; Spinella, Philip C.; Doctor, Allan
Abstract : Objectives: To provide context for the implementation of the Pediatric Critical Care Transfusion and Anemia Expertise Initiative recommendations for RBC transfusions including a review of prior research related to implementation of transfusion guidelines, efforts to facilitate implementation through Transfusion and Anemia Expertise Initiative, and to provide a framework for recommendation implementation. Design: Review of existing clinical literature and description of a comprehensive approach to implementation based on Implementation Science principles. Results: The Transfusion and Anemia Expertise Initiative recommendations on RBC transfusions are based on clinical evidence and aim to limit unnecessary and potentially harmful transfusions. Prior efforts to use transfusion guidelines include use of provider education, local guidelines, visual aids, prospective and retrospective audit and feedback as well as computerized decision support tools; however, no single approach has been identified as optimal for implementation in pediatric critical care settings. Evidence around provider beliefs and transfusion decision-making point to the need for additional provider education, emphasizing the importance of limiting transfusions, and the development of recommendations, such as the Transfusion and Anemia Expertise Initiative guidelines, that can be applied to specific clinical conditions. Conclusions: The Transfusion and Anemia Expertise Initiative guidelines will be broadly disseminated; however, coordinated implementation efforts will be required to impact practice. An approach that encourages involvement of a wide range of multiprofessional stakeholders, formal agreement on the implemented guidelines, selection of strategies that are practical and feasible, and active monitoring of clinical practice and outcomes throughout implementation is recommended. A formal second stage Transfusion and Anemia Expertise Initiative - Continuous Assessment of Blood-use is proposed to enhance implementation of the recommendations, follow uptake and impact on practice and patient outcomes, and ensure integration of new clinical evidence into the existing guideline as it is developed.